Learning as moments of friction and opportunity: an autoethnography of ECR identities in queer time. Issue 4 (September 2021) - Weatherall, Ruth; Ahuja, Sumati
In this article, we explore how time and temporality shape the identities of early career researchers as they learn to become academics. We engage in a collaborative autoethnography to reflect on how our shared identities as middle-class women and our divergences in age, ethnicity, familial status and sexuality shaped our embodied experiences of becoming academics. Drawing on the concept of queer time, we reconceptualise the becoming of newcomers as they learn (or do not learn) to belong to academia. We illustrate how queer time interrupts normative ideas of newcomer learning as progress, development and reproduction. We suggest that learning may alternatively be understood as 'moments of friction' and 'moments of opportunity' in which newcomers to the academy feel out of step, out of place and out of time . We conceptualise these moments as simultaneously painful yet productive of possibilities for learning to become an academic, differently.